Childbirth Self-Efficacy and Its Associated Factors among Pregnant Women in Arba Minch Town, Southern Ethiopia, 2023: A Cross-Sectional Study - Tesfahun Simon; Kassahun Fikadu; Bezawit Afework; Habtamu Alemu; Begetayinoral Kussia (Hindawi Limited, 2024)
Background. Childbirth self-efficacy is a pregnant women's perception of their ability to cope with labor stress. Low childbirth self-efficacy is linked to pain intolerance and poor labor progression, which increase the possibility of operative delivery. However, Ethiopia has limited data. So, the aim of this study was to assess childbirth self-efficacy and its factors among pregnant women attending antenatal care in public health facilities in Arba Minch town, Southern Ethiopia, in 2023. Objective. To assess childbirth self-efficacy and associated factors among pregnant women attending antenatal care in public health facilities in Arba Minch town, Southern Ethiopia, in 2023. Methods. An institution-based cross-sectional study was carried out among 416 women from January 1 to January 30, 2023. A systematic random sampling technique was employed. Data were collected by KoboToolbox through face-to-face interviews using a structured and pretested questionnaire. Modified short-form childbirth self-efficacy inventory was used to score self-efficacy. The Statistical Package for Social Sciences, version 27, was used for data management and analysis. Descriptive statistics were calculated for each variable, and a logistic model was used. Statistical significance was determined at a p value of less than 0.05 and 95% confidence level. Results. A total of 416 pregnant women participated in the study. Two hundred twenty-eight (54.8%) of the pregnant women had low childbirth self-efficacy. Age group in ≤24 years (AOR=3.80, 95% CI: 1.82-8), primigravida (AOR=1.51, 95% CI: 1.10-2.86), unplanned pregnancy (AOR=1.67, 95% CI: 1.02-2.70), poor social support (AOR=2.17, 95% CI: 1.09-4.30), having anxiety (AOR=1.30, 95% CI: 1.10-3.64), having poor knowledge of childbirth (AOR=2.21, 95% CI: 2.09-5.39), and severe fear of childbirth (AOR=6.40, 95% CI: 2.60-9.80) were statistically significant with low childbirth self-efficacy. Conclusions. The magnitude of low childbirth self-efficacy was high in the study area. Being primigravida, unplanned pregnancy, age≤24 years, severe fear of childbirth, anxiety, poor social support, and poor knowledge were significantly associated with low childbirth self-efficacy. Therefore, giving special attention to these factors during antenatal care would be important.